Tinjauan Yuridis Terhadap Kreditor Konkuren Dalam Hal Tercapainya Perdamaian Dalam PKPU - Wijaya, Nini Putri; Widjaja, Gunawan; Rusli, Hardijan (LAW REVIEW, 2004)
Now a days, where the economy has not fully recovered from crisis yet, business and entrepreneurs must be extra careful in carrying out their business. Many have been forced to shut down their business due to their incapability in paying out debts that are already due. If a businessman/ debtor has more than one creditor and one of the debts are already, then by request of the creditor, the debtor can be filed bankrupt. This is regulated by Indonesian Bankruptcy Law article I (1). As a reaction to this, the law has provided the debtor an alternative way put, that is by Suspension of Payment.  Suspension of Payment is a request made by the debtor to the court to give a period of time to suspend the payment of the debt which is due because of certain reasons. This is regulated by article 212 Indonesia Bankruptcy law. In the Suspension of Payment , many parties beside the debtor is involved, among other are the creditors, which consist of three kinds of creditor who are: unsecure creditor, creditor with security, and creditor with special right. By having this Suspension of Payment, the creditor with security  who has the right to execute their security, must be suspended for a period of time until the verdict of the court is resulted. The rights of that creditor is only suspended, not dismissed until the judged gives out a verdict of either bankruptcy or reconcilement means. After the verdict is resulted, that creditor can execute their rights, which can  unbenefit the debtor and the unsecured creditor. Because of the Indonesian Bankruptcy law has not yet given enough protection, that is why the Indonesian government still discussed the new Indonesian Bankruptcy Law, hopefully can give enough protection to all parties. However, this study typologically falls into the category of normative legal  research. Therefore, this research is qualitative in nature and mainly uses literary method in gathering the data required. Further, those data were processed with other stipulating and related laws and regulation.